2015
DOI: 10.1152/jn.00486.2015
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping representations for reach depth and direction in caudal superior parietal lobule of macaques

Abstract: -Reaching movements in the real world have typically a direction and a depth component. Despite numerous behavioral studies, there is no consensus on whether reach coordinates are processed in separate or common visuomotor channels. Furthermore, the neural substrates of reach depth in parietal cortex have been ignored in most neurophysiological studies. In the medial posterior parietal area V6A, we recently demonstrated the strong presence of depth signals and the extensive convergence of depth and direction i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
46
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
2

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 81 publications
7
46
0
Order By: Relevance
“…Here, we have found that more anterior regions in the parietal cortex corresponding to SPLp and, at lower thresholds, SPLa and SPLr contained neural populations tuned to eye movement direction. These findings are in line with previous studies that found that neurons in medial posterior parietal cortex in the monkey are modulated by both eye direction and depth (Hadjidimitrakis et al, 2015;Breveglieri et al, 2012). Our findings suggest that these areas are not only coarsely sensitive to the difference between eye movements performed towards the left or right, but that the underlying neural populations show properties that are compatible with directional tuning.…”
Section: Areas Representing Eye Movement Directionsupporting
confidence: 93%
“…Here, we have found that more anterior regions in the parietal cortex corresponding to SPLp and, at lower thresholds, SPLa and SPLr contained neural populations tuned to eye movement direction. These findings are in line with previous studies that found that neurons in medial posterior parietal cortex in the monkey are modulated by both eye direction and depth (Hadjidimitrakis et al, 2015;Breveglieri et al, 2012). Our findings suggest that these areas are not only coarsely sensitive to the difference between eye movements performed towards the left or right, but that the underlying neural populations show properties that are compatible with directional tuning.…”
Section: Areas Representing Eye Movement Directionsupporting
confidence: 93%
“…This suggests that these cells are tuned to respond to objects only when they are within a limited range of DTC or TTC. A similar tuning of cell responses to distance in response to looming stimuli is found in the ventral intraparietal area (VIP) of the PPC in non-human primates ( Colby et al, 1993 ; Graziano and Cooke, 2006 ; see also Hadjidimitrakis et al, 2015 ), as well as in the premotor cortex (PMC, Graziano et al, 1997 ). Graziano ( Graziano and Cooke, 2006 ) has proposed that such cells may play a role in defensive and avoidance behavior.…”
Section: Discussionsupporting
confidence: 55%
“…This area contains an incomplete representation of the body, mainly focused on upper and lower limbs, without an evident topographic organization (Breveglieri et al, 2006(Breveglieri et al, , 2008. It has been recently demonstrated that a large percentage of PEc neurons encodes both direction and depth information during arm reaching movements (Hadjidimitrakis et al, 2015), and contributes to hand-target transformations for reaching (Piserchia et al, 2016). In contrast, area PE (which has been traditionally equated to Brodmann's area 5) contains an almost complete representation of the body, with a coarse topographic organization (Taoka et al, 1998(Taoka et al, , 2000Padberg et al, 2007).…”
mentioning
confidence: 99%